Pengaruh Marketing Mix (4P) dan Perilaku Konsumen Terhadap Niat Pemilihan Program Studi Teknik Metalurgi - Marya Delima Pasaribu; Mariana Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2024)
The research aims to determine the influence of the marketing mix (4P) and consumer behavior on the intention to choose the Metallurgical Engineering study program. Analysis using Structural Equating Modeling (SEM) on Partial Least Square (PLS) and data collection by distributing questionnaires to 150 respondents who know Metallurgical Engineering, Institute Del Technology. Purposive sampling is the sampling method used in research. The research results show that the intention to choose a Metallurgical Engineering study program is strongly influenced by the marketing mix (4P) and consumer behavior.